WILL DOING A LOT OF PROMOTIONS HELP INCREASE IMAGE AND CONSUMER APPEAL? - Zaenal Aripin; Eko Aristanto; Ngurah Made Novianha Pynatih (Journal of Economics, Accounting, Business, Management, Engineering and Society, 2023)
The rapid development in the world of marketing shows that promotion is not only a tool to increase sales, but also has a significant impact on the company's image and consumer appeal. The fundamental question arises: whether by doing a lot of promotion, companies can effectively improve their image and strengthen the appeal to consumers. This study aims to investigate whether the intensity of promotion contributes to the improvement of company image and consumer appeal. By focusing on the relationship between promotion frequency and consumer perception, this study aims to provide a deeper understanding of the effects of promotion on company image and the extent to which it affects consumer appeal. This study uses a Systematic Literature Review (SLR) approach to collect and analyze related research findings from various literature sources. Taking into account empirical research, consumer theory, and corporate case studies, the study details the impact of promotion on corporate image and consumer appeal. Analysis of the literature reveals that promotions done wisely can make a positive contribution to improving a company's image and consumer appeal. The right frequency of promotions, consistent messaging, and timeliness are key factors in shaping consumers' positive perception of the brand. However, keep in mind that excessive or irrelevant promotions can result in negative impacts, such as consumer fatigue and decreased trust.